2016
DOI: 10.14214/sf.1573
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the coverage and annual variation in bilberry yield in Finland

Abstract: Highlights• The highest bilberry coverage was found in mesic heath forests and fell forests.• On peatlands the coverage was, on average, lower than on mineral soil sites.• The approach introduced in this study to calculating annual berry yield indices is a promising way for estimating total annual bilberry yields over a given period of time. AbstractThe coverage of bilberry (Vaccinium myrtillus L.) was modelled as a function of site and stand characteristics using the permanent sample plots of the National For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The fresh weight of bilberry shoots was predicted as a function of site and stand characteristics by using a bilberry coverage model. The following model (without stand age as a predictor) was fitted based on the same data that were used by Turtiainen et al [20]:…”
Section: Bilberry Shootsmentioning
confidence: 99%
“…The fresh weight of bilberry shoots was predicted as a function of site and stand characteristics by using a bilberry coverage model. The following model (without stand age as a predictor) was fitted based on the same data that were used by Turtiainen et al [20]:…”
Section: Bilberry Shootsmentioning
confidence: 99%
“…, Turtiainen et al. , Nilsson and Cory ). This finding might suggest one reason, in addition to the possible higher predation risk and low understorey cover that plantations, in contrast to old forests, seem to be unsuitable habitats for grouse broods (Kastdalen and Wegge , Moss and Oswald , Miettinen et al.…”
Section: Discussionmentioning
confidence: 97%
“…These characteristics also appear in younger forests and may have confused the modelling because the forest classes known to have negative effects on grouse occurrences, such as clear-cut areas and seedlings, were not included as explanatory variables in the model. It has been found that on mineral soils the cover provided by blueberry bushes increases with forest stand age and basal area and decreases strongly during regeneration cuttings (Tonteri et al 2016;Turtiainen et al 2016;Nilsson and Cory 2017). Because recently regenerated stands have lower understory cover and higher predation risks, grouse brood survival is better in old forest stands (Kastdalen and Wegge 1985;Moss and Oswald 1985;Miettinen et al 2010;Melin et al 2016).…”
Section: Discussionmentioning
confidence: 99%